Standards Monitoring Study, 1990 - Braithwaite, John (ADA Dataverse, 2019)
The Standards Monitoring Study was undertaken with the broad aim of achieving a better understanding of implementation of the nursing home outcome standards, which the Commonwealth government introduced in July 1987. The study sampled two populations, all persons who had worked as a standards monitor in the Australian Commonwealth's standards monitoring process since 1987, and all persons who were working as managers in the standards monitoring process in the Department of Community Services and Health in 1990. Variables were similar for each of the sampled populations and included attitudes to outcome standards; perceptions of useful tools and approaches for motivating compliance with the standards; the ranking of reasons for not meeting nursing home standards; and attitudes to nursing homes and standards monitoring teams. Background variables include state; sex; employment status; occupation and educational attainment.